The Bacteroides fragilis Toxin Binds to a Specific Intestinal Epithelial Cell Receptor - Wu, Shaoguang (American Society for Microbiology, 2006)
The Bacteroides fragilis toxin (BFT) is the only known virulence factor of enterotoxigenic B. fragilis. BFT has previously been shown to act, at least in part, through cleavage of the intercellular adhesion protein E-cadherin. A specific cellular receptor for BFT has not been identified. The goal of this study was to determine if the initial interaction of BFT with intestinal epithelial cells was consistent with binding to a specific cellular receptor. Purified BFT was labeled with a fluorophore or iodide to assess specific cellular binding and the properties of BFT cellular binding. BFT binds specifically to intestinal epithelial cell lines in vitro in a polarized manner. However, specific binding occurs only at 37°C and requires BFT metalloprotease activity. The BFT receptor is predicted to be a membrane protein other than E-cadherin or a known protease-activated receptor (PAR1 to PAR4). BFT binding is resistant to acid washing, suggesting an irreversible interaction. Sugar or lipid residues do not appear to be involved in the mechanism of BFT cellular binding, but binding is sensitive to membrane cholesterol depletion. We conclude that intestinal epithelial cells in vitro possess a specific membrane BFT receptor that is distinct from E-cadherin. The data favor a model in which the metalloprotease domain of BFT processes its receptor protein, initiating cellular signal transduction that mediates the biological activity of BFT. However, activation of recognized protease-activated receptors does not mimic or block BFT biological activity or binding, suggesting that additional protease-activated receptors on intestinal epithelial cells remain to be identified.